2019
DOI: 10.1155/2019/6593736
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Moderate to Severe Pain during the First 24 Hours after Laparoscopic Bariatric Surgery While Receiving Intravenous Patient-Controlled Analgesia

Abstract: Objective To investigate the incidence of and risk factors for moderate to severe pain during the first 24 hours after laparoscopic bariatric surgery. Materials and Methods This retrospective study included morbidly obese patients who underwent laparoscopic sleeve gastrectomy or Roux-en-Y gastric bypass at a single institution between June 2016 and July 2018. Demographic, clinical, operative, and postoperative pain data from the postanesthesia care unit (PACU) and ward were analyzed. Intravenous patient-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…The finding of this study is in line with Arissara Iamaroon et al who reported the incidence of POP as 75% within 24 h of the post-operative period. 7 However, Tania casino et al and other study showed that less POP incidence with our result. 8,9 The differences were due to the timing of the pain assessment and the study area.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The finding of this study is in line with Arissara Iamaroon et al who reported the incidence of POP as 75% within 24 h of the post-operative period. 7 However, Tania casino et al and other study showed that less POP incidence with our result. 8,9 The differences were due to the timing of the pain assessment and the study area.…”
Section: Discussioncontrasting
confidence: 58%
“…The finding of this study is in line with Arissara Iamaroon et al who reported the incidence of POP as 75% within 24 h of the post-operative period. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Our results are clinically important as pain remains to be poorly controlled after surgery [27][28][29][30]. Adequate postsurgical pain control has been correlated with improved patient satisfaction [31,32].…”
Section: Discussionmentioning
confidence: 97%
“…Several publications stated that obesity was not associated with postoperative pain. 4,7,17 This was probably due to the pharmacokinetics of analgesia drugs. 18 The metabolism of morphine was not altered in the morbidly obese when compared with normal volunteers.…”
Section: Discussionmentioning
confidence: 99%